New studies on network frequency responses considering dynamic loads - L. T. M. Trang; H. Nouri (International Journal of Applied Power Engineering (IJAPE), 2019)
The dynamic model construction of transmission network components that include generator buses, load buses and power branches, within MATLABSimulink environment is presented. The degree of frequency deviation of buses when the power of motor loads and static loads vary, is studied. Furthermore, the influence of motor loads with different inertia constants are considered in the control technique of load frequency using a PID controller. The results show that the frequency oscillation of the dynamic load is greater than the frequency oscillation of static load. Also the speed of frequency control of the dynamic load is greater than the speed of the frequency control of the static load and the inertia constants of the dynamic load has significant influence on the frequency control characteristics.